Lingual and stylistic peculiarities of new borrowed Anglicisms in Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article outlines the lingual and stylistic peculiarities of Anglicisms that emerged in English and were borrowed to the Ukrainian literary language in the 1990s and 2000s: the revealed features are stylistic devices, cognitive characteristics, paradigmatic relations and stylistic coalescences in the borrowed neologisms.
Keywords: Anglicism; neologism; borrowing; stylistic device; paradigmatic relation